Merce Cunningham Dance Company Review from the Festival's Anniversary Season - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review from the Dance Umbrella Festival's Anniversary Season. PALABRAS CLAVE: Merce Cunningham Dance Company, Events.
Dentro del apartado "Silver Jubilee: Dance Umbrella at 25".